La Ley del Procedimiento Administrativo General después del Decreto Legislativo N.º 1272: diez modificaciones pendientes para una Administración más predecible - Montenegro Monteza, Favio Martín (Pontificia Universidad Católica del Perú, 2025)
The article examines the reforms introduced by Legislative Decree No. 1272 to Peru’s General Administrative Procedure Law (LPAG) and proposes ten amendments to enhance its effectiveness and predictability. Key suggestions include: extending expiration rules to the appeal stage, applying LPAG provisions to oversight activities, suspending all measures when appeals are filed, reinforcing reasoning in administrative acts, safeguarding the use of reconsideration, clarifying the scope of voluntary correction, standardizing measure terminology, fixing the tax unit (UIT) based on the date of the offense, regulating mitigating factors for non-monetary sanctions, and removing the requirement for new evidence in certain reconsiderations. These improvements aim to reduce arbitrariness, ensure legal certainty, and optimize administrative performance.

El artículo analiza las reformas introducidas por el Decreto Legislativo N.º 1272 a la Ley del Procedimiento Administrativo General (LPAG) y propone diez modificaciones para fortalecer su eficacia y predictibilidad. Entre ellas destacan: ampliar la caducidad a la etapa recursiva, aplicar transversalmente la LPAG a la fiscalización, suspender todas las medidas al interponer recursos, reforzar la motivación de los actos, proteger el uso de la reconsideración, precisar el alcance de la subsanación voluntaria, clarificar la nomenclatura de medidas, fijar la UIT según la fecha de infracción, regular atenuantes para sanciones no pecuniarias y eliminar la exigencia de nueva prueba en ciertas reconsideraciones. Estas mejoras buscan reducir la arbitrariedad, garantizar seguridad jurídica y optimizar la actuación administrativa.
The General Administrative Procedure Act after Legislative Decree No. 1272: ten pending amendments for a more predictable public administration
Keywords: Expiration; Oversight; Voluntary correction; Legal certainty; Sanctioning procedure; Caducidad; Fiscalización; Subsanación voluntaria; Seguridad jurídica; Procedimiento sancionador; https://purl.org/pe-repo/ocde/ford#5.05.00